Construction of evaluation index system of water resources carrying capacity based on ecological civilization - Wang, Xiaoyan; Gao, Jinjuan; Jiang, Han; Li, Shuangquan (Frontiers in Environmental Science, 2025)
Ecological civilization construction is an important way to achieve sustainable development in China. To reconcile the contradictions between water resources and rapid economic growth in China, it is essential to establish a scientific and rational evaluation index system for water resources carrying capacity (WRCC) based on the concept of ecological civilization. This study first delves into the connotation of WRCC and constructs a theoretical framework for the WRCC evaluation index system under the guidance of ecological civilization. Then, correlation analysis and information contribution rate analysis are employed to optimize the index system. Finally, a comprehensive and representative evaluation index system for WRCC is formed. Taking the Henan section of the Yellow River Basin as an example, the results are as follows: (1) A WRCC evaluation index system with 4 target layers, 10 criterion layers, and 43 indicator layers is established; (2) The WRCC in the study area exhibits a general upward trend; (3) Key obstacles to WRCC development include water resources per capita (X2), precipitation (X1), groundwater resources per unit area (X3), ecological water use rate (X19) and forest coverage rate (X20). Future efforts should prioritize mitigating water resource pressure and enhancing ecological environment protection. This study provides a reference for establishing an effective WRCC evaluation index system and holds significant practical implications for guiding the sustainable development of regional water resources.